Towards the Digital Coaching: Personalization, Opportunities and Challenges - El Houcine El Bazi et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Digital life coaching has frequently been discussed within wellness, health and sport life coaching, emerged with the practices of Human Potential Movement (HPM), (Spence, 2007) and from humanistic traditions of psychology (Maslow, 1954). Many studies show that with the development of technology, life coaching starts to attract individuals who wish to achieve their personal and professional goals, it also assists them in recognizing their strengths, aspirations and challenging. The foundation of this discipline is due to the work of Albert Ellis as psychologist who is considered as one of the founders of cognitive-behavioural approach therein he prefigures life coaching. In fact, during the late 1980s and early 1990s, Thomas Leonard, popularly known as the father of professional life coaching, had raised the profile of coaching life. After him Thomas Leonard, known as the "father of coaching,". He played a major role in defining the modern coaching as a distinct profession during the decency 1980s and 1990s. He is also the founder of the first formal coaching organizations, including the International Coach Federation (ICF) and Coach University. His philosophy is focused on six principles: Self- Discovery and Empowerment, Focus on Personal fulfilment, values-based coaching, creating systems and tools, focus on balance and the coach-client partnership In fact, after its foundation until today, the role of the life coaching with digital version is adopted as new alternative and strategy aiming to support individuals to create action plans and move forward with a real and practical collaborative process focused on self-discovery, personal growth, accountability and goal setting.